Sehl, Thomas: my Air Force recollections (September 22, 1978) - Sehl, Thomas, b. 1899; Main, Chris D. (1978)
Interviewer: Main, Chris D.; Rank: Wing Commander. ; Interviewee: Sehl, Thomas, b. 1899; An interview/narrative of Thomas Sehl's experiences during World War I. Wing Commander Sehl served with the Royal Flying Corps/Royal Air Force and the Royal Canadian Air Force. Interview took place on September 22, 1978.; ABSTRACT: Wing Commander Thomas Sehl Royal Flying Corps/Royal Air Force Royal Canadian Air Force